Cartera de crédito vencida de la Cooperativa de Ahorro y Crédito “Virgen del Cisne”, agencia Vinces en el periodo 2019-2020. - Rodríguez Chevez, Jefferson Rolando (2022)
In this case study, a comparison will be made of the overdue credit portfolio of the Virgen del Cisne Savings and Credit Cooperative, Vinces agency during the years 2019-2020, which has a problem, that of arrears in payments. of credits from customers. In the organization there are well-defined credit policies that prevent credits from being granted to clients who do not have the ability to pay, but sometimes those in charge of approving the credits do not carry out a very exhaustive study and analysis of the data and issue credits to customers with little ability to pay, also as there was a pandemic, customer credit payments were late due to the fact that many of them lost their jobs or became ill, this situation allowed the overdue credit portfolio and the index of delinquency of the cooperative has undergone changes, for which this case study will be carried out in order to know how the credit portfolio varied before and during the pandemic. The methods to be used in this research are the deductive and analytical method through observation, interview and literature review techniques. It is feasible to carry out this case study because it will have a better understanding of the organization's nonperforming loan portfolio and how it undergoes changes during a natural event.